2022
DOI: 10.3389/fpubh.2022.915965
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19 among homeless individuals in Germany in mid-2021

Abstract: AimsTo investigate the prevalence and the correlates of fear of COVID-19 among homeless individuals.MethodsWe used data from the “national survey on psychiatric and somatic health of homeless individuals during the COVID-19 pandemic” (NAPSHI-study) which took place in several large cities in Germany in Mid-2021 (n = 666 in the analytical sample). Mean age equaled 43.3 years (SD: 12.1 years), ranging from 18 to 80 years. Multiple linear regressions were performed.ResultsIn our study, 70.9% of the homeless indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…A German study from 2021 indicated low fear of COVID-19 among PEH. They also described higher fear of COVID-19 among PEH aged 50 to 64 (49) which is the main age group in our cohort and might explain the mainly positive attitude toward the COVID-19 vaccination. That age might have a strong impact on the attitude toward vaccine attitude is also mentioned by a Danish study von COVID-19 vaccine coverage among PEH.…”
Section: Discussionsupporting
confidence: 51%
“…A German study from 2021 indicated low fear of COVID-19 among PEH. They also described higher fear of COVID-19 among PEH aged 50 to 64 (49) which is the main age group in our cohort and might explain the mainly positive attitude toward the COVID-19 vaccination. That age might have a strong impact on the attitude toward vaccine attitude is also mentioned by a Danish study von COVID-19 vaccine coverage among PEH.…”
Section: Discussionsupporting
confidence: 51%